Laparoscopic Removal of Angelchik Prosthesis Followed by Interval Sleeve Gastrectomy. (21st May 2019) - Afridi, Faryal G.; Johnson, Morgan; Musgrove, Kelsey A.; Abunnaja, Salim; Tabone, Lawrence E.; Borgstrom, David C.; Szoka, Nova
Abstract : Introduction . The Angelchik prosthesis (AP) is a historic antireflux device which consists of a C-shaped silicone ring placed around the gastroesophageal junction (GEJ) and secured by Dacron tape. We present a rare experience with an AP and its impact on bariatric surgical outcomes. Case . Our patient is a 66-year-old woman who had an open antireflux procedure with an AP in 1987. She presented to a bariatric clinic for consideration of bariatric surgery for the treatment of morbid obesity and associated comorbidities. She also reported significant problems with reflux and dysphagia. After an appropriate work-up, an AP was identified at her GEJ. She was taken to the operating room for laparoscopic removal with planned interval laparoscopic sleeve gastrectomy. Intraoperatively, the AP was identified around the GEJ; after extensive adhesiolysis, the prosthesis was removed. Postoperatively, in order to determine if the AP had caused any lasting esophageal motility problems, the patient underwent a high-resolution esophageal manometry which demonstrated normal esophageal motility. Interval laparoscopic sleeve gastrectomy was performed safely 9 weeks later. Conclusion . Although rarely used, it is still possible to encounter an Angelchik prosthesis in practice. General and bariatric surgeons need to be aware of this rare device and understand how to manage its related complications.